Efektifitas Penggunaan Metode Problem Solving dalam Mencapai Hasil Belajar Fisika SMP Negeri 3 Leihitu - Latukau, Randi Hasim; Edi Saputra, I Gede Purwana; Fatmalasari L, Rizky; Permana, Imam; Azmar, Azmar (Al-Khazini, 2021)
This research was conducted in an effort to improve the quality of student learning outcomes at SMP Negeri 3 Leihitu by applying the Problem Solving method. Problem Solving applied in this study focused on the ability of students to deal with problems and determine problem solving solutions. Students are encouraged to be creative, active and responsive to problems related to physics subjects, especially on Forced material. The type of this research used is quantitative descriptive research. The sample of this study was class VIII1students, totaling 30 students. The effectiveness of learning in this study can be known after analyzing the test results, namely pre-test and post-test. The effectiveness of achieving student competency standards was analyzed using the t-test. After analyzing the data, the results showed that learning with problem solving methods was very effective because it was through the t-test where the thit value was 22.13 which wasobtained through the ttab value of 2.042. Meanwhile, in the cognitive, affective, and psychomotor aspects of students with this method, it can be seen that the level of mastery increased significantly with the percentage of completeness of 96.66%.